Improving the quality of education at the secondary level - a case study on Jazan schools in the Kingdom of Saudi Arabia (The International Journal of Educational Sciences and Arts, 2023)
The main issue that preoccupies the Kingdom of Saudi Arabia in the field of education is how to formulate the educational process that makes the student at this stage keep pace with the great scientific developments and be able to deal with all global changes and developments and move from education to learning and from education as a stage to continuous learning. In order to improve the quality of secondary schools, we must identify the requirements for improving the quality of secondary schools, and what are the problems that can be faced to prevent them from improving their quality, and how they can be overcome. The current research tried to present proposals for improving the quality of secondary schools in the Kingdom of Saudi Arabia.This research seeks to find solutions to the problems of education at the secondary level. So, there was an urgent need to know how to improve the quality of secondary schools in Saudi Arabia. The research ended with a set of proposals that contribute positively to this field.
Keywords: Secondary schools; education problems; quality of education; quality control tools